Priest. - Bird, Anotnia; Roache, Linus; Wilkinson, Tom, 1948-; Carlyle, Robert, 1961- (Burbank, Calif : Miramah Home Entertainment, 1996)
A young Roman Catholic Priest in a liverpool Parish must learn to deal with the issues of homosexuality and incest, as well as conflicts between his vows and his conscious.
" DVD Copy"
Keywords: Feature films -- Great Britain -- Drama; Priests -- England -- Drama; Gay clergy -- England -- Drama; Celibacy -- Catholic Church -- Drama; Celibacy -- Catholic Church; Gay clergy; Priest -- Drama